Pengelolaan Peralatan Praktik Menggunakan Asset Inventory System Berbasis Ubiquitous dan Cloud Computing pada Program Keahlian Geologi Pertambangan dan Geospasial SMKN 1 Balikpapan - Fatmawati Fatmawati; Totok Sulistyo; Karmila Achmad; Mariatul Kiptiah; Desak Made Ristia Kartika; Widodo Widodo (Abdimas Universal, 2023)
In the Mining Geology and Geospatial expertise program, practical learning is mostly conducted outdoors or in the field. This means that there is a high flow of equipment in and out of use, and students' negligence can cause damage to the equipment. Additionally, manual management of practice tools can be inefficient and result in losses, which can hinder the learning process. To address these issues, an online tool management system based on ubiquitous computing is proposed. This system can be accessed on various devices such as computers, androids, and smart TVs. The research begins with a preparatory phase that involves surveying user requirements. The implementation phase involves data analysis, application design, testing, and software implementation, followed by maintenance and further development. By using this system, practical tools can be tracked, and the advantages of the application can be accessed anywhere and anytime. This facilitates the administration of borrowing and returning practice tools at the workshop for Mining Geology and Geospatial SMKN 1 Balikpapan.